Mathematical Creative Thinking Ability: Its Relation to Study Independence and Self-Concept - Nurdin Nurdin; Zaid Zainal; Erni Erni; Dian Anugrah; Khaerani Nurdin (Universitas Negeri Makassar, 2024)
This study constitutes a quantitative research endeavor aimed at examining the influence of self-directed learning and self-concept on mathematical creative thinking ability. A questionnaire was used as the measuring tool during the data gathering process. The questionnaire was employed to gather data on self-directed learning and self-concept, while tests were utilized to collect data on mathematical creative thinking ability. Questionnaires were used as the assessment tool for data collecting. The questionnaire was utilized to capture data on self-directed learning and self-concept, while tests were employed to gather data on mathematical creative thinking ability. Data analysis utilized both descriptive and inferential statistics. Descriptive statistics were employed to ascertain the mean, median, mode, and standard deviation. The research findings indicate that the levels of self-directed learning, self-concept, and creative mathematical thinking abilities among elementary school students in the Malili district fall within the moderate category. There exists an influence of self-directed learning on students' creative mathematical thinking abilities. Additionally, there is an influence of self-concept on students' creative mathematical thinking abilities. Furthermore, self-directed learning and self-concept impact students' math creativity. Conclusion: there is a significant influence of both self-directed learning and self-concept on mathematical thinking abilities, both partially and collectively.